2017
DOI: 10.1159/000481864
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Predictors of Satisfaction in Patients with Improved Lithium Disilicate All-Ceramic Crowns

Abstract: Objectives: The aim of this study was to determine the clinical outcomes and predictors of satisfaction in patients with lithium disilicate (LD) ceramic crowns. Subjects and Methods: Clinical outcomes were assessed in 47 patients with 88 LD crowns using modified United States Public Health Service (USPHS) evaluation criteria and survival rates. The questionnaire for predictors included 3 aspects: (a) sociodemographic characteristics, (b) oral health habits (tooth brushing frequency, flossing frequency, and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…A possible explanation of these findings can be derived from the fact that LAVA Zr milling undergoes post milling sintering for milling (soft machining) efficiency of Zr substructure, resulting in a linear shrinkage of nearly 20%. 22 However there are compensatory mechanisms in the software and scanning process, sintering is a possible cause for increased discrepancies in the marginal fit and internal adaptation of zirconia frameworks, as shown in the present study. A systematic review by Abduo et al, concluded that Zr framework fit discrepancies are related to soft machining, curvatures and long framework spans.…”
Section: Discussionmentioning
confidence: 51%
“…A possible explanation of these findings can be derived from the fact that LAVA Zr milling undergoes post milling sintering for milling (soft machining) efficiency of Zr substructure, resulting in a linear shrinkage of nearly 20%. 22 However there are compensatory mechanisms in the software and scanning process, sintering is a possible cause for increased discrepancies in the marginal fit and internal adaptation of zirconia frameworks, as shown in the present study. A systematic review by Abduo et al, concluded that Zr framework fit discrepancies are related to soft machining, curvatures and long framework spans.…”
Section: Discussionmentioning
confidence: 51%
“…An acceptable and clinically successful restoration must display adequate fit and adaptation, shape and contours, esthetic appearance with shade matching, and suitable hygienic contacts. Poor fit and adaptation lead to micro leakage and secondary caries, however shape and contour errors cause asymmetry and plaque accumulation [ 9 , 10 , 11 ]. Fabrication of acceptable esthetic restoration requires the integration of several critical factors, including an individual’s perception of color and the environment during visual shade selection, knowledge of dental anatomy, compatibility with materials, preparation designs, and accurate impressions [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we believe that the results of the study by Samer et al [1] should be interpreted with caution.…”
mentioning
confidence: 79%
“…Dear Editor, It is with great interest that we read the article by Samer et al [1] published in Medical Principles and Practice in October 2017. The authors designed and conducted a cross-sectional study to determine the predictors of satisfaction in patients with improved lithium disilicate (LD) all-ceramic crowns among a Malaysian population.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation